Acute health effects of the Tasman Spirit oil spill on residents of Karachi, Pakistan - Najam-; Khuwaja Urooj; Farooqui Sadia; Nawaz Haq; Kasi Pashtoon; Janjua Naveed; Jafri Syed; Lutfi Shahid; Kadir Muhammad; Sathiakumar Nalini (BMC, 2006)
Abstract Background On July 27 2003, a ship carrying crude oil run aground near Karachi and after two weeks released 37,000 tons of its cargo into the sea. Oil on the coastal areas and fumes in air raised health concerns among people. We assessed the immediate health impact of oil spill from the tanker Tasman Spirit on residents of the affected coastline in Karachi, Pakistan. Methods We conducted a study consisting of an exposed group including adults living in houses on the affected shoreline and two control groups (A and B) who lived at the distance of 2 km and 20 km away from the sea, respectively. We selected households through systematic sampling and interviewed an adult male and female in each household about symptoms relating to eyes, respiratory tract, skin and nervous system, smoking, allergies, beliefs about the effect on their health and anxiety about the health effects. We used logistic regression procedures to model each symptom as an outcome and the exposure status as an independent variable while adjusting for confounders. We also used linear regression procedure to assess the relationship exposure status with symptoms score; calculated by summation of all symptoms. Results Overall 400 subjects were interviewed (exposed, n = 216; group A, n = 83; and group B, n = 101). The exposed group reported a higher occurrence of one or more symptoms compared to either of the control groups (exposed, 96% vs. group A, 70%, group B 85%; P < 0.001). Mean summary symptom scores were higher among the exposed group (14.5) than control group A (4.5) and control group B (3.8, P < 0.001). Logistic regression models indicated that there were statistically significant, moderate-to-strong associations (Prevalence ORs (POR) ranging from 2.3 to 37.0) between the exposed group and the symptoms. There was a trend of decreasing symptom-specific PORs with increase in distance from the spill site. Multiple linear regression model revealed strong relationship of exposure status with the symptoms score (β = 8.24, 95% CI: 6.37 - 10.12). Conclusion Results suggest that the occurrence of increased symptoms among the exposed group is more likely to be due to exposure to the crude oil spill.